Immobilization Effects of Anticell and Antiaxial Filament Sera on Treponema zuelzerae - Bharier, M. A. (1971)
Rabbit antisera were produced against whole cells and against highly purified axial filaments of Treponema zuelzerae. Both types of sera react with axial filaments. Antisera against whole cells immobilize the organism; antisera against axial filaments do not. The immobilizing activity of anticell sera could be neutralized by preabsorption with whole cells but not by preabsorption with axial filaments. Preabsorption with axial filaments did, however, abolish the ability of anticell sera to react with axial filaments. Anticell sera also react with the outer cell envelope; this ability was not affected by preabsorption with axial filaments. The data show that antibody directed at something other than axial filaments causes immobilization of T. zuelzerae. The results do not exclude the possibility that the axial filament is the organelle of motility. Titration of the immobilizing activity of anticell sera by adding a constant amount of motile cells to serial dilutions of serum gave two zones of maximum immobilization, one with undiluted serum and one at higher dilutions. For a fixed amount of antiserum, increasing the numbers of cells in the titration almost, but not quite, abolished the zone phenomenon. This phenomenon appears to result from the presence of two kinds of immobilizing antibodies in anticell serum. One of these belongs to the IgG class of immunoglobulins. The other has not been identified but is present in a serum globulin fraction which contains IgM. At intermediate concentrations, the “IgM fraction” inhibits the immobilizing activity of IgG without itself causing immobilization.